Genome-wide identification and response stress expression analysis of the BES1 family in rubber tree (Hevea brasiliensis Muell. Arg.) - Bingbing Guo (PeerJ, 2022)
Brassinolide (BR) plays an important role in plant growth, development, and the adaptation adversity process. Moreover, BRI1-EMS-SUPPRESSOR 1 (BES1) genes are crucial transcription factors (TFs) in the BR signaling pathway. To realize the function of HbBES1 family is helpful to improve genetic resources for rubber tree breeding. Based on the rubber tree database, we used bioinformatics to characterize physicochemical properties, gene structure, cis-elements, and expression patterns. These results indicated that there were nine BES1 members in rubber tree, which we named HbBES1-1 to HbBES1-9 and divided into two groups (I and II) based on their genetic relationships. HbBES1 genes in the same group shared similar gene structures and motifs. Cis-acting element analysis showed that the promoter sequences of HbBES1 genes contained many regulator elements that were related to hormone and stress, indicating that HbBES1 genes might be involved in the regulation of hormone and stress signal pathways. Our analysis of tissue specificity revealed that all of the nine HbBES1 members expressed highly in branches. Gene expression profiles under different hormone treatments showed that the HbBES1 gene family was induced to varying degrees under different hormones, HbBES1-3 and HbBES1-9 were extremely induced by ethylene (ETH). These results lay the foundation for further exploration of the molecular mechanism of the BES1 gene family, especially HbBES1-3 and HbBES1-9, regulating plant stress tolerance in rubber tree.